Macroeconomic Fluctuations in Sub-Saharan Africa - Hoffmaister, Willy (Washington, D.C. : International Monetary Fund, 1997)
The sources of macroeconomic fluctuations in sub-Saharan African are examined by comparing the CFA franc countries with the non-CFA franc countries. External shocks, especially terms of trade shocks, appear to have a greater influence on fluctuations of output and the real exchange rate in CFA franc countries. This result does not appear to be associated with differences in the economic structure but may reflect the fixed exchange rate regime, which does not (partially) buffer these countries from external shocks. Macroeconomic fluctuations in non-CFA franc countries are similar to those in other developing countries, particularly in Latin America.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet